Gamification Tools in Higher Education: Creation and Implementation of an Escape Room Methodology in the Pharmacy Classroom - Ana Isabel Fraguas-Sánchez; Dolores R. Serrano; Elena González-Burgos (Education Sciences, 2022)
Educational escape rooms have emerged as an excellent active learning tool to improve student learning, motivation, and engagement. In this work, a methodology to design and develop escape rooms in the classroom has been established and implemented within the general pharmacology, biopharmacy and pharmacokinetics, and pharmaceutical technology disciplines for pharmacy students. Each escape room consisted of three sequential challenges that the students had to solve, and we divided the students into groups of 3–6 participants to complete a mission containing educational questions related to the curriculum of each module. The escape rooms were successfully implemented in all these disciplines, and the activity was positively evaluated by the students (>95% satisfaction). They allowed the students to apply the theoretical learning outcomes of each subject. Moreover, escape rooms promoted teamwork and improved the problem-solving skills of the students. For an escape room to be successful and meet the established learning outcomes, challenges must be adapted to the target students, the time should be precisely set, the tasks of the game master should be well-defined, and final feedback should be included in the session.